Effects of Inadvertent Oral Ingestion of Jatyadi Oil (AYUSHDHARA, 2024)
Ayurveda offers various formulations for different ailments, including Jatyadi oil, a topical medicine commonly used for wounds and ulcers. While it’s local application is well-documented for conditions like sinuses, papules, dermatitis, wounds, ulcers, burns, and abrasions, its oral ingestion is not standard practice due to potential adverse effects. Objective: This report aims to highlight the consequences of inadvertent oral ingestion of Jatyadi oil by a patient. Methods: The case report is based on a real-life incident involving a patient who mistakenly ingested Jatyadi oil. The effects were studied by discussing the matter with the patient and reviewing relevant literature. Conclusion: While medications are meant to heal, incorrect usage can lead to harm. Although accidental oral intake of Jatyadi oil may not be overly concerning, it is crucial to avoid such occurrences. Patients should be properly instructed regarding the correct dose, route, and method of medication intake to prevent such incidents.